Influence Of Product Quality, Location And Price Perception On Customer Satisfaction (Study At Lemona Cake Shop On Perintis Kemerdekaan Street) - Patimah, Euis; Yusnita, Rita Tri; Lestari, Suci Putri (Journal of Management, Economic, and Accounting, 2023)
This study aims to determine the simultaneous and partial effect of Product Quality, Location and Price on Lemona Bakery's Customer Satisfaction. The research method used in this study is a quantitative research method with a survey approach. The sampling technique used was incidental sampling and 100 respondents were taken as a sample. The analytical tool used is the multiple regression equation. The results showed that product quality, location and price perceptions simultaneously had a significant effect on customer satisfaction at Lemona Bakery. Product quality partially has a significant effect on customer satisfaction at Lemona Bakery. Location partially has a significant effect on customer satisfaction at Lemona Bakery. Perceived price partially has a significant effect on customer satisfaction at Lemona Bakery.